(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Between October 2014 and January 2021 was analyzed for climatological variables such as: air temperature (maximum and minimum), soil temperatures and relative humidity. In general, it was observed that the air temperature within the secondary forest had lows of 11°C and highs of 29.4°C; while in forest patches under restoration, differences were observed, below 12°C and close to 42°C. At maximum and minimum temperatures it was observed that the greatest oscillations were outside the secondary forest relict in patches under restoration (varying by 11°C, mean of 16.9°C vs. by 10°C, average of 16°C within the forest). The soil temperature is higher in patches under restoration and outside the forest (mean 18.2°C) than inside (mean 16.8°C), except in 2018; however, its variation overlaps in both sampling stations (outside 10.0-29.0°C and inside 11.0-25.0°C). Relative humidity was found to be higher (average 75.6%) within the secondary forested relict than outside in patches under restoration (average 71.4%); also within the secondary forested relict, values were observed between 28.0% and 100%, outside the forest in patches under restoration variations between 18.0% and 99.0% were noted, relative humidity data close to 20% were recorded in 2018, and close to 90-100% in 2019.